กระบวนการใช้สื่อในการเผยแพร่ข้อมูลและรับฟังความคิดเห็นของประชาชนเกี่ยวกับการปฏิรูปการศึกษาของสำนักงานปฏิรูปการศึกษา (ส.ป.ศ.) - ชัยสิทธิ์ ศรีธวัช ณ อยุธยา (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The objectives of this study is to study the process of media usage for publicity and public hearing about the educational reforming of the office of education reform (OER) in the period of 2000 - 2001. The study found that the processes of media usage for publicity and public hearing about the educational reforming of the office of education reform (OER) are the communication for understanding and agreement in the educational reform by the public relation strategies, considering to the strong point for each media. The mass media are preferred to use for publicize the information in one-way communication. Printed media and journal are the main choices, the next below is broadcasting media. The human media is using both publicity the information and public hearing in two-way communication via any special events, to meet with the target group. The majority of people agree with the educational reform’s policies of OER. Because of the lack of practical motivation from the government, the educational reforming campaign is not success completely.